KESALAHAN SISWA SMP DALAMA MENYELESAIKAN SOAL PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Sumoked, Jeyni R.; Kumesan, Selvie; Manorfa, Mono (SOSCIED, 2025)
This research is backgrounded by the difficulty of students in solving problems on the material of the system of linear equations of two variables. This research uses descriptive quantitative analysis techniques, namely by steps 1) Data collection, 2) Data reduction, 3) data presentation, 4) conclusion drawing. The data were collected through a written test in the form of 5 essay questions and interviews conducted with 3 students, as well as distributing questionnaires to all students based on Polya's theory. This study aims to determine the types of errors and the causes of these errors. The subjects used in the study were class students IX A SMP Negeri 1 Tondano totalling 26 students. The results showed that students made errors at the reading stage by 67%, developing a plan by 50%, implementing the plan 59.23%, and checking back by 84.61%. Errors are caused by several factors such as the habit of students who do not record important information contained in the problem, lack of accuracy in reading the problem, inability to put the problem into mathematical form, difficulty continuing the planning made and not being accustomed to checking back the results of the answers obtained and drawing conclusions from the answers that have been obtained.